Contexts between apple orchards with various cultivar comparisons and the effect of ATS (ammoniumthiosulphate) on fruit thinning - Csihon, Ádám (Acta Agraria Debreceniensis, 2013)
Our research focuses on a fruit thinning material that can also be used in apple production. This material reduces significantly the required manual labor of hand thinning by russeting the blossoms selectively. The ATS (ammonium-thiosulphate) acts as chemical desiccant contrary to the nowadays commonly used materials such as naphthalene acetic acid, naphthyl acetamide, benziladenin and ethylene, which affect the metabolic processes of the plant by regulating the hormone system. In our experimentals cultivar ’Pinova’ and ’Golden Reinders’ were treated with different concentrations of ATS. The effect of these doses on the fruit setting and the quality and quantity parameters of the fruits was studied. According to our results, in the case of cultivar ’Pinova’ the ATS did not have any detected effects at the concentration of 1.5%. Application of ATS at 3% decreased considerably the fruit setting and fruit yield, accordingly the mean fruit size improved. The response to treatment in the case cultivar ‘Golden Reinders’ does not have any similar consistent results.